KEEFEKTIFAN PUNTUNG ROKOK SEBAGAI PENGENDALI Gloeosporium fructigenum PADA BUAH APEL ( EFFECTIVITY OF CIGARETTE BUTTS AS CONTROL AGENT OF Gloeosporium fructigenum ON APPLE) - Suharti, Woro Sri; Wachjadi, Muljo; Feti, Ruth (Pembangunan Pedesaan, 2010)
The objective of the research was to determine the effectivity of cigarette butts extract to control the growth of Gloeosporium fructigenum causing apple bitter rot in vitro and in vivo. Randomized block design was used with factorial pattern for both in vitro and in vivo treatments. The first factor for in vitro treatment was kinds of solvent, i.e., water and ethanol. The second one was type of cigarette consisted of filtered cigarette butts, non-filtered cigarette butts and sliced tobacco. The third factors were the concentration of cigarette butts extract, and sliced tobacco (10, 30, and 50%). The first factor for in vivo treatment was concentration of non-filtered cigarette butts extract with water solvent (10, 20, and 30%), the second one was fruit soaking time (10, 15, and 20 minutes). Variables measured on in vitro research were diameter of the fungi, conidia size, and inhibition of conidial growth. Variables measured on in vivo one were incubation period, area of symptoms, effectiveness of cigarette butts extracts, rate of infection, and sensory test. The research results showed that the extract of non-filtered cigarette butts and sliced tobacco both with water and ethanol as a solvent had ability to inhibit the growth of G. fructigenum in vitro. Filtered cigarette butts extract was effective to control the G. fructigenum in vivo